A magyar ipar főbb sajátosságai az abszolút specializáció tükrében - Komarek, Levente (Jelenkori Társadalmi és Gazdasági Folyamatok, 2011)
During the past few years the territorial issues of the location of industry came to the forefront both in Hungary and in the European Union. On certain areas of our country different industry structures evolved and various industries became dominant in each region. The actuality of the topic is enhanced by the fact that now adays has become an important key issue to rationalize the structure of industry. Therefore it is all the more necessary to do research in Hungary for the investigation of the structural changes of industry as well as to examine and analyse the correlations to ensure the developm ent of rational and efficient industrial structure on the given areas. This is also very important, because regional specialization is a quality- indicator category, which to a certain extent, refers to the development level of the region as well. In addition can be expected in modern market economies that the areas be specialised in the industrial sectors, where there are more favourable production conditions